SALAFIYYUDIN REFUTATION TOWARD YUSUF AL QARDHAWI CONCEPT OF DEMOCRACY - Agung Wibawa (Metakom, 2020)
Conflict of thoughts concerning to the concept of democracy to this day continues. In one hand, Islamic groups known as salafiyyun reject this concept for democracy does not originate from the teachings of the islamic religion and is a concept adopted from the West so that it is not suitable for use. In another hand, the moderate islamic groups represented by an Egyptian Ulama Yusuf Qardhawi support the concept of democracy as an alternative for the realization of a better society. This sharp discrepancy raises the text of the Salafiyyun group to criticize the concept of democracy from Yusuf Qardhawi in the rubric manhaj in www.salafy.or.id with the title “Penyimpangan Pikiran Yusuf Al Qardhawi (I). This Research applies discourse analysis methode according to Teun A. Van Dijk. This model was chosen because it looks at the scheme and reveals the “how” within a text or massage .